EXISTENTIAL PARADIGM IN SOCIAL WORK: LIMITATIONS AND POTENTIALITY - Bogdanova, Natalija; Švedaitė-Sakalauskė, Birutė (Acta Paedagogica Vilnensia, 2010)
Since the search of the meaning of life sounds unusual as a definition of social work practice, it is necessary to bring to mind existential model of social work which copes with unanswered existential needs that can determine a wide range of social problems. This article discusses the core of existential social work and analyses why this model is not well developed and not fit to everyday practice. The method of the research is analysis, synthesis and interpretation of two studies of existential social work. In the first part of the article the interpretation of theoretical perspectives is presented. The perspective of D. F. Krill shows existential social work as a personal therapy based on philosophy of existentialism and existential psychotherapy. The second, N. Thompson’s, constructs a broader sociological trend to extend individual approach to the social theory. Despite different attitudes towards existential theory in social work both authors agreed about social worker’s personal existential creed in a helping process. In the second part set limitations of existential model are analyzed. It was shown that existential social work is not developed enough and used by practitioners due to the following: requirements for the personality of a social worker; necessity for both special theoretical knowledge and practice skills that lead to another problem of professional identification of a social worker; weak possibility to work with those clients who have limited competence of introspection and self-reflection; expensiveness of existential social work practice. Finally, the last but not the least problem is the high dependence of social work on social policy and political hand which tends for neoliberalization at present time. Against the odds, existential paradigm is significant for social work practice. On top of all that existential theory allows to analyse critically processes that take place in contemporary society and turn back to clients as persons who have vital needs for the meaning of life.